Peruvian Botanical Biopesticides for Sustainable Development and Protection of the Environment - Bracho-Pérez, J. (2019)
Daphnia magna is proposed as a bioindicator to establish the minimum concentration capable of controlling pests before performing toxicity tests. This study uses the proposed pest control extracts of two Peruvian species, Clibadium peruvianum Poepp. (seeds) and Petiveria alliacea L. (leaves). The toxicological effects of the plant extracts were evaluated with D. magna, using five neonates over a period of 24–48 h. A lack of mobility or the absence of heart rhythm for 15 s under a stereomicroscope was considered to indicate mortality. Organic extracts were discarded due to their higher toxicity when compared with the aqueous extracts of C. peruvianum and P. alliacea, which had LC50 = 460.74 mg/L and LC50 = 711.18 mg L−1 at a concentration of 10 mg L−1, respectively. Using this Daphnia-safe concentration, toxicity tests were performed on the third instar larvae of Musca domestica (housefly). Higher activity was observed with an aqueous extract of seeds of C. peruvianum and a leaf aqueous extract of P. alliacea, showing 58.33% and 56.7% mortality against M. domestica, respectively. Both extracts induced abnormal changes in the development of the housefly, causing deformation, burns, and dehydration of tissues in the larvae. It is evident that using D. magna as a preliminary toxicological test allows the determination of concentrations that are safer to use while maintaining the activity of the extracts as a botanical biopesticide, thus posing the lowest risk to the environment, ecosystems, their species, and human health.